2022
DOI: 10.2298/tsci210612317h
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis and optimization of L-shape fin heat sink under natural convection using ANOVA and Taguchi

Abstract: Advancement in electronic systems resulted in miniaturization and high-power densities. Therefore, the rate of heat generation in circuit board increased dramatically. To overcome the problem of overheating, numerous heat sink designs are proposed including L-shape fins heat sink. The thermo-fluidic flow behavior and temperature difference are analyzed to get better understanding of heat transfer from the sink to ambient air. Governing equations for the model of conjugate heat transfer in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Additionally, it was found that the average Thermal Design Power (TDP) is 95 watts for Intel i9 9900k according to the Intel data sheet [25]. Another source mentioned that Intel core i9 9900k, at 5 GHz, never really crossed the 100 watts limit [26].…”
Section: Boundary Conditions and Necessary Assumptionsmentioning
confidence: 99%
“…Additionally, it was found that the average Thermal Design Power (TDP) is 95 watts for Intel i9 9900k according to the Intel data sheet [25]. Another source mentioned that Intel core i9 9900k, at 5 GHz, never really crossed the 100 watts limit [26].…”
Section: Boundary Conditions and Necessary Assumptionsmentioning
confidence: 99%